Review: Management Technology Transfer in the Indonesian Pharmaceutical Industry - Sumayyah, Shofiah; Resca Harda, Adila; Aliza Putriana, Norisca (Indonesian Journal of Pharmaceutics, 2023)
Thisreviewarticlefocusesontechnologytransferinthepharmaceuticalindustry,specifically discussingits importance,guidelines, process, and documentation intheIndonesiancontext.Thepurposeis toprovideadetailedunderstandingoftechnologytransfer from drug discovery to product development, including the reasons for its utilizationanditssignificanceinthepharmaceuticalsector.Themethodologyemployedforthisreview involvedsearching onlineliterature throughplatformssuchasScienceDirectandGoogleScholarusingkeywordslike"TransferTechnology"and "Pharmaceutical Development." Thefindings of the primary sources emphasizethecrucialroleoftechnologytransferinfacilitatingthegrowth ofthepharmaceuticalindustry. Itenables theavailabilityof essential technologiesin developing countries,promotingaccessibilityandaffordability.Threekeyfactorscontributetoeffectivetechnologytransfer:properplanning,involvementofcapableindividuals,andawell-definedprocess.Successintechnologytransfernecessitatesacomprehensiveunderstandingoftheprocessandtheabilitytopredictitsfutureperformanceaccurately.Furthermore,thearticleemphasizestheimportanceofensuringrobustandeffectivemanufacturingprocessesfordrugsubstancesanddrugproducts.Thisincludesproducingthesesubstancesandproductsincompliancewithregisteredspecifications and adhering to Good Manufacturing Practices Keywords: Transfer technology, Pharmaceutical development, Research and development, Pharmaceutical industry.